2019
DOI: 10.7554/elife.44186
|View full text |Cite
|
Sign up to set email alerts
|

Glial Ca2+signaling links endocytosis to K+ buffering around neuronal somas to regulate excitability

Abstract: Glial-neuronal signaling at synapses is widely studied, but how glia interact with neuronal somas to regulate their activity is unclear. Drosophila cortex glia are restricted to brain regions devoid of synapses, providing an opportunity to characterize interactions with neuronal somas. Mutations in the cortex glial NCKXzydeco elevate basal Ca2+, predisposing animals to seizure-like behavior. To determine how cortex glial Ca2+ signaling controls neuronal excitability, we performed an in vivo modifier screen of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 87 publications
1
40
0
Order By: Relevance
“…Hence, SIK3 is required for an effective glial response to a K + stress. K + dynamics play a critical role in modulating neuronal activity, and dysfunctional glial K + regulation promotes neuronal hyperexcitability in seizure patients and in mouse and fly models of seizure (Bedner et al, 2015;Weiss et al, 2019). Here we tested whether glial SIK3 has a non-cell autonomous impact on axonal excitability at the larval neuromuscular junction (NMJ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, SIK3 is required for an effective glial response to a K + stress. K + dynamics play a critical role in modulating neuronal activity, and dysfunctional glial K + regulation promotes neuronal hyperexcitability in seizure patients and in mouse and fly models of seizure (Bedner et al, 2015;Weiss et al, 2019). Here we tested whether glial SIK3 has a non-cell autonomous impact on axonal excitability at the larval neuromuscular junction (NMJ).…”
Section: Resultsmentioning
confidence: 99%
“…To explore in vivo Ca 2+ dynamics in PG cells, we expressed a myristoylated variant of Ca 2+ -sensitive GFP (myr::GCaMP6s) to monitor Ca 2+ in fine processes 24,27 with the PG driver GMR85G01-gal4 28 (hereafter referred to as PG-gal4). We first performed imaging experiments in live, undissected 2 nd instar larvae as previously described 27 .…”
Section: Dynamic Ca 2+ Transients Occur In Perineurial Glia In Vivomentioning
confidence: 99%
“…We recently found that chronic Ca 2+ increase in Drosophila cortex glia predispose animals to stimulation-induced seizures 24 , while acute increases in intracellular Ca 2+ in Drosophila astrocyte-like glia drives neuronal silencing 22 . To identify glial signaling pathways that may modulate neuronal excitability, we performed a genetic screen using the pan-glial driver repo-gal4 to drive expression of RNA interference (RNAi) targeting ~850 genes encoding membrane receptors, secreted ligands, ion channels and transporters, vesicular trafficking proteins and known cellular Ca 2+ homeostasis and Ca 2+ signaling pathway components 24 . This screen revealed that pan-glial knockdown of dStim led to severe HS-induced seizures-like episodes (Video 4, middle and Figure 4A, S2A), similar to those we previously identified in NCKX zyd (zyd) mutants that disrupt a Ca 2+ ion exchanger in cortex glia 24,27 .…”
Section: Genetic Screening Reveals Glial Knockdown Of Dstim Increasesmentioning
confidence: 99%
See 2 more Smart Citations